A Comparison of Cloud Execution Mechanisms: Fog, Edge and Clone Cloud Computing - Tina Francis; Dr. Muthiya Madhiajagan (IAES Indonesia Section, 2017)
Cloud computing is a technology that was developed a decade ago to provide uninterrupted, scalable services to users and organizations. Cloud computing also became an attractive feature for mobile users due to the limited features of mobile devices. The combination of cloud technologies with mobile technologies gave a new area of computing called mobile cloud computing. This combined technology is used to augment the resources existing in smart devices. In recent times Fog computing, Edge computing and Clone Cloud computing techniques have become the latest trends after mobile cloud computing, which have all been developed to address the limitations in cloud computing. This paper reviews these recent technologies in detail. This paper also addresses the differences in these technologies and how each of them are effective to organizations and developers.Cloud computing is a technology that was developed a decade ago to provide uninterrupted, scalable services to users and organizations. Cloud computing also became an attractive feature for mobile users due to the limited features of mobile devices. The combination of cloud technologies with mobile technologies gave a new area of computing called mobile cloud computing. This combined technology is used to augment the resources existing in smart devices. In recent times Fog computing, Edge computing and Clone Cloud computing techniques have become the latest trends after mobile cloud computing, which have all been developed to address the limitations in cloud computing. This paper reviews these recent technologies in detail. This paper also addresses the differences in these technologies and how each of them are effective to organizations and developers.Cloud computing is a technology that was developed a decade ago to provide uninterrupted, scalable services to users and organizations. Cloud computing also became an attractive feature for mobile users due to the limited features of mobile devices. The combination of cloud technologies with mobile technologies gave a new area of computing called mobile cloud computing. This combined technology is used to augment the resources existing in smart devices. In recent times Fog computing, Edge computing and Clone Cloud computing techniques have become the latest trends after mobile cloud computing, which have all been developed to address the limitations in cloud computing. This paper reviews these recent technologies in detail. This paper also addresses the differences in these technologies and how each of them are effective to organizations and developers.